2015
DOI: 10.1371/journal.pone.0138153
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Alpha Oscillations in the Human EEG with Facial Preference

Abstract: Facial preference that results from the processing of facial information plays an important role in social interactions as well as the selection of a mate, friend, candidate, or favorite actor. However, it still remains elusive which brain regions are implicated in the neural mechanisms underlying facial preference, and how neural activities in these regions are modulated during the formation of facial preference. In the present study, we investigated the modulation of electroencephalography (EEG) oscillatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
1
15
1
Order By: Relevance
“…However, not every aspect of the preference prediction process through thin-slicing could be represented in scalp EEG. Many previous studies reported that frontal areas such as mPFC are primarily involved in the self-referential processing (Frith and Frith, 1999 , 2003 ; Vogeley et al, 2001 ; Kampe et al, 2003 ; Platek et al, 2004 ; Boksem and Smidts, 2015 ; Jack and Schyns, 2015 ; Kang et al, 2015 ), which was not present in the EEG data of this study. Nevertheless, our results may suggest importance of the self-referential information processing for individual performance of others' preference prediction.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…However, not every aspect of the preference prediction process through thin-slicing could be represented in scalp EEG. Many previous studies reported that frontal areas such as mPFC are primarily involved in the self-referential processing (Frith and Frith, 1999 , 2003 ; Vogeley et al, 2001 ; Kampe et al, 2003 ; Platek et al, 2004 ; Boksem and Smidts, 2015 ; Jack and Schyns, 2015 ; Kang et al, 2015 ), which was not present in the EEG data of this study. Nevertheless, our results may suggest importance of the self-referential information processing for individual performance of others' preference prediction.…”
Section: Discussioncontrasting
confidence: 62%
“…EEG beta oscillations have been implicated in the prediction of one's preference over movie and musical tempo (Popova et al, 2014 ; Kang et al, 2015 ). Northoff et al, also suggested that self-referential information processing in the social domain was reflected in neural activity over the regions of mPFC, ACC, temporal pole and superior temporal sulci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants did not focus on the experiment tasks of the vMMN, so the alpha composition was activated during the unattended process. Moreover, the modulation of human EEG activity by facial preference was found in the alpha band power (8–13 Hz) but not in the other frequency bands (Kang et al, 2015 ). A study also showed differential alpha coherence hemispheric patterns in males and females during pleasant and unpleasant musical emotions (Flores-Gutiérrez et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%